Gettering and defect engineering in semiconductor technology XV - Murphy, J. D. (Diffusion and defect data. Solid state phenomena, 2014)
The book includes both fundamental and technological aspects of defects in semiconductor materials and devices, including photovoltaics. The 74 papers are grouped as follows: I. Defect engineering in silicon solar cells; II. Structural and production issues in cast silicon materials for solar cells; III. Characterisation of silicon for solar cells; IV. Intrinsic point defects in silicon; V. Light impurities in silicon-based materials; VI. Metals in silicon: fundamental properties and gettering; VII. Extended and implantation-related defects in silicon; VIII. Surfaces, passivation and processin.